Gramatyczna kategoria liczby w przedgramatycznej tradycji filozoficznej Grecji (Grammatical Category of Number in Pre-grammatical Philosophical Tradition of Greece) - Wolanin, Hubert (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The aim of the paper is to present the way in which the grammatical category of number was referred to by the Greeks before its description took the standard shape known particularly from the Τέχνη γραμματική, attributed to Dionysios Thrax. The research in this field shows that it was Aristotle who first pointed to this category in the 20th chapter of his Poetics, where the expression πτῶσις κατὰ τὸ ἑνὶ ἢ πολλοῖς [σημαῖνον] presents it as one of the bases of word variance peculiar to the name (ὄνομα) and verb (ῥῆμα). The next references to the category of number, already designated with the term ἀριθμοί (‘numbers’), are to be found in the Stoic lingustic doctrine. On the one hand, we come across them when specific classes of words (parts of speech) are being described, which is to say the verb (ῥῆμα), defined as a part of speech signifying something relating to one or many [objects], and the article (ἄρθρον), which is described as a part of speech discerning the genders and numbers of names, whereby the category of number was shown from an apecific relative perspective, i.e. as a characteristic of objects, which are implied by the semantics of a verb, and as a characteristic of names, which finds its indicator in the article. On the other hand, within this branch of Stoic logic, which includes discussions about things signified by the language, the syntactic features of the verb’s number (and person), i.e. following (or not) the rules of agreement with the number (and person) of the nominal exponent of the subject of predication, were given the status of a criterion of the classification of predicates expressed by the very verbs; on the basis of this criterion, the predicate of the σύμβαμα kind contrasts with the παρασύμβαμα one.